Thoracoscopic epicardial ablation of atrial fibrillation: Safety, efficacy, single center experience - Troubil, Martin; Simek, Martin; Juchelka, Jan; Steriovsky, Andrea; Hajek, Roman; Santavy, Petr (Biomedical papers, 2023)
Aims. Atrial fibrillation (AF) is associated with reduced quality of life and increased risk of ischaemic cerebrovascular events. The left atrial epicardial ablation procedures have evolved towards a successful and safe rhythm control strategy for patients with symptomatic drug-refractory paroxysmal, persistent or post-ablation AF or with a high risk of catheter ablation failure. The aim was to evaluate the efficacy and safety of thoracoscopic ablation at our instituiton. Methods. We observed 81 patients undergoing thoracoscopic ablation from January 2015 to December 2019. Results. The mean age was 61.3 extpm8.5 years and the average duration of AF was 3.1 extpm2.6 years. The cohort consisted of 16.5% of paroxysmal AF, 36.7% persistent, and 46.8% of long-standing AF. The procedure was completed in 79 patients; during follow-up, 15 patients (19%) received radiofrequency ablation. Freedom from atrial arrhythmia recurrence was 55.7% after a follow-up (FUP) period of 3.1 extpm1.4 years. At the follow-up visit, sinus rhythm was present in 81% of patients. No relationships between arrhythmia recurrence and BMI, LVEF, left atrial dimension, gender, and AF duration were found. Major complications were noticed in 4 patients (5.0%); 2 had peripheral embolisation, 2 patients were converted to a sternotomy. At the time of the FUP visit, 25.3% of patients were using antiarrhythmic and 74.7% were still using anticoagulants. Conclusion. In the majority of patients, sinus rhythm remained despite a considerable atrial tachycardia recurrence rate, with a relatively low percentage of patients on antiarrythmic drugs.
Keywords: atrial fibrillation; thoracoscopic ablation; rhythm